2014
DOI: 10.1177/1367549414526733
|View full text |Cite
|
Sign up to set email alerts
|

Non-media-centric media studies: A cross-generational conversation

Abstract: On the face of it, the notion of non-media-centric media studies appears to be a contradiction in terms. Surely those who are working in media studies will put media at the centre of their investigations and explanations of social life? In the following conversation, three advocates of a non-media-centric approach discuss their ways into the field of media studies at different points in its development, and together they explore their overlapping empirical research interests as well as their theoretical, metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 43 publications
0
32
0
1
Order By: Relevance
“…The general interest of their exploration, beyond optimization of the knowledge interest of their own figurational project, has to do with finding a best practice for the non-mediacentric understanding of media use in the life-world. Following the call for nonmediacentric media research of David Morley (2009); Zlatan Krajina et al (2014) and others, their study is essentially devoted to the solving of the age-old so-called Observer's Paradox; that is, the fact that the aim of ethnographic research is to find out how people are behaving when they are not being systematically observed-yet this can only be done by observing them systematically (Labov 1972: 209). Therefore, all research that engages people in the collection of data is intrusive and subject to bias.…”
Section: Methodological Media-centrism and Nonmedia-centrism In Figurmentioning
confidence: 99%
“…The general interest of their exploration, beyond optimization of the knowledge interest of their own figurational project, has to do with finding a best practice for the non-mediacentric understanding of media use in the life-world. Following the call for nonmediacentric media research of David Morley (2009); Zlatan Krajina et al (2014) and others, their study is essentially devoted to the solving of the age-old so-called Observer's Paradox; that is, the fact that the aim of ethnographic research is to find out how people are behaving when they are not being systematically observed-yet this can only be done by observing them systematically (Labov 1972: 209). Therefore, all research that engages people in the collection of data is intrusive and subject to bias.…”
Section: Methodological Media-centrism and Nonmedia-centrism In Figurmentioning
confidence: 99%
“…9. There is a long discussion in media and communication research about the necessity of such a 'non-mediacentric' perspective on transforming communications that does not always consider media as the angle of change (see recently Couldry 2006;Morley 2009;Moores 2012;Krajina et al 2014). We refer here to the argument that only research which…”
Section: 1)mentioning
confidence: 99%
“…Um exemplo dessa tradição é o trabalho de Raymond Williams, que analisou a centralidade da (ideia de) cultura na sociedade burguesa como um processo histórico (Williams, 1961), desenvolvendo perspectivas histórico-materialistas que lhe permitiram estudar a televisão como uma "forma social" (Williams, 1974). Um outro exemplo é o trabalho de David Morley, que tem vindo a "descentrar" os estudos dos média, contribuindo para aquilo que mais recentemente tem chamado de non media-centric e more-than-representational media studies (Krajina et al, 2014). Miller e Maxwell retomam vários aspectos desta tradição -as questões de textualidade, discurso e representação (privilegiadas nos estudos culturais); as questões de recepção, significação e usos (centrais aos active audience studies); e as questões de produção, propriedade e controlo (objecto da economia política dos média) -para configurar um ambicioso programa interdisciplinar que pretende articular níveis de análise "macro" (instituições, regiões, estruturas) e "micro" (experiências, práticas, textos) através de um trabalho colaborativo que envolve semiólogos, teóricos e críticos da cultura, antropólogos, geógrafos, sociólogos, etnógrafos, atravessando fronteiras disciplinares entre humanidades e ciências sociais, conhecimento académico e não académico.…”
Section: Conclusãounclassified